Soybean protein hydrolysate-formaldehyde-urea block copolymer for controlled release fertilizer. Issue 1 (1st January 2019) - Liu, Na; Qu, Ping; Huang, Hongying; Wei, Zhengying
ABSTRACT: Urea formaldehyde (UF) was modified by the soybean protein hydrolysate (SPH) to adjust the rate of nitrogen, phosphorus, and potassium (NPK) release. The SPH section can copolymerize into the UF molecules. The crystallinity of modified UF fertilizer decreased with increasing SPH content. The surface of SPH-modified UF fertilizer was loose and porous. The nitrogen content of SPH-modified UF fertilizer decreased a little, but the nitrogen, phosphorus and potassium release rate was improved with increasing SPH content in modified fertilizer. The grain number per ear, thousand-grain weight and total yield were improved by the SPH-modified UF fertilizer. Compared to UF and control, protein, starch, fat, soluble sugar and vitamin C in the maize were increased by applying SPH-modified UF fertilizer. The results indicated that the nutrient release behavior can be adjusted by the introduced SPH to match the maize needs.